A New Method for Accurate and Efficient Modeling of the Local Ocean Induction Effects. Application to Long‐Period Responses from Island Geomagnetic Observatories. Issue 8 (27th April 2020) - Chen, Chaojian; Kruglyakov, Mikhail; Kuvshinov, Alexey
Abstract: There is significant interest in constraining mantle conductivity beneath oceans. One data source to probe oceanic mantle conductivity is magnetic fields measured at island observatories. From these data local responses are estimated and then inverted in terms of conductivity. However, island responses may be strongly distorted by the ocean induction effect (OIE) originating from conductivity contrasts between ocean and land. Insufficiently accurate accounting for OIE may lead to wrong interpretation of the responses. OIE is generally modeled by global simulations using relatively coarse grids to represent bathymetry. We explore whether very local bathymetry influences island responses. To address this question we developed a methodology for efficient modeling of effects of bathymetry of any resolution. On an example of two island observatories we demonstrate that small‐scale bathymetry dramatically influences the responses. Using new methodology we obtain new conductivity models beneath considered islands and observe very good agreement between modeled and experimental responses. Key Points: A global‐to‐Cartesian (G2C) electromagnetic (EM) modeling tool was developed to account for effects in long‐period responses from local bathymetry Model studies using the G2C tool show that local bathymetry dramatically influences responses at island geomagnetic observatories G2C makes it possible to explain anomalous behavior of the experimental responses at island observatories